PENGARUH DESAIN PRODUK DAN STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK - Dwiningwarni, SS; Anjarsari, Nur Maya; Syuhada', H. (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
This study aims to  analyze the impact of product design and marketing strategy to the purchasing decision partially, analyze the influence of design and marketing strategies on purchasing decisions simultaneously,  determine which variables are the dominant influence on purchasing decisions. The research approach used is positivism with quantitative data derived from respondents' answers collected through questionnaires. The method used is the Focus Group Discussion (FGD). The sampling technique used was simple random sampling and the number of samples taken as many as 100 respondents. Analysis of the data used is multiple linear regression with Ordinary Least Square method (OLS). The results of this study are the design of the product and marketing strategies significantly influence purchasing decisions partially, product design and marketing strategies significantly influence purchasing decisions simultaneously,  product design dominant influence on purchasing decisions. This means that companies must pay attention to the shape or design of a product to be manufactured or produced.